Kurdish Novice English Language Teachers’ Perceptions on their Teaching Practices and Needs: A Case Study - Salh, Sevar Saeed (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
The present study aimed to investigate into Kurdish novice English language teachers’ perceptions on their teaching practices and needs. The study also aimed to identify their perceptions on the teacher education programs they had gone through and to what extent they had prepared them for the process of teaching. For this purpose, the teachers’ perceptions regarding their difficulties, challenges and needs in their first year(s) of teaching were identified. This study is a mixed method case study, which applies a descriptive -interpretive method. Sixty – three Kurdish novice English teachers who are teaching in basic and preparatory schools of General Educational Directorate of Erbil participated in this study. Thirty – three teachers were from the basic level while thirty teachers were teaching in preparatory level. Both qualitative and quantitative data were collected from two different sources: teacher questionnaire and teacher interviews. The results of the study indicate that in general, Kurdish novice English language teachers found some aspects in their first year(s) of teaching difficult, some neither difficult nor easy and some others easy. The results also show that teaching about target culture, hiring practices and dealing with special needs of students were their main problems. The results at the same time show that the teachers were in need of support from their administrators, interaction with experienced English teachers and a continuous training program. As regards the teacher education program, the results show that teacher education program they completed did not fully satisfy them and they believed that their needs were not met. Based on the results, some implications for improving the teacher education in Kurdistan regional government of Iraq and suggestions for further studies have been recommended. The implications can help teacher education programs to be more effective and help novice teachers more to face less problems and provide them with their needs.

ÖZ: Bu çalışma, Kürt asıllı yeni İngilizce öğretmenlerinin öğretmenlik uygulamalarına ve ihtiyaçlarına ilişkin algılarını araştırmayı amaçlamaktadır. Buna ek olarak, bu çalışma mezun oldukları öğretmen eğitim programları hakkındaki algılarını ve onları öğretme süreci için ne ölçüde hazırladıklarını araştırmayı amaçlamaktadır. Bu amaç doğrultusunda, öğretmenlerin meslekteki ilk yıllarında yaşadıkları, zorluklar ve ihtiyaçlarla ilgili algıları belirlenmiştir Bu çalışma, tanımlayıcı-yorumlama yöntemini kullanan bir durum çalışmasıdır. Bu çalışmanın katılımcıları, Erbil'in Genel Eğitim Müdürlüğünün temel ve hazırlık okullarında eğitim veren 63 Kürt asıllı yeni İngilizce öğretmeni idi. Bunlardan 33'ü temel seviyede öğretmen iken, 30 öğretmen ise hazırlık düzeyinde ders vermiştir. Hem nicel hem de nitel veriler iki farklı kaynaktan toplanmıştır: öğretmen anketi ve öğretmen görüşmeleri. Çalışmanın sonuçları, genel olarak, Kürt yeni İngiliz dili öğretmenlerinin ilk öğretim (ler) in bazılarında zor, bazıları ne zor ne de kolay, bazılarında da kolay bulduklarını göstermektedir.Sonuçlar ayrıca, hedef kültürü öğretme, işe alma uygulamaları ve öğrencilerin özel ihtiyaçları ile ilgilenmenin temel problemler olduğunu göstermektedir. Sonuçlar aynı zamanda, öğretmenlerin idarecilerden destek almaları, deneyimli İngilizce öğretmenleriyle etkileşim ve sürekli bir eğitim programı alma gibi gereksinimleri olduğunu göstermektedir. Öğretmen eğitimi programı ile ilgili olarak, sonuçlar öğretmenlerin tamamladıkları öğretmenlik eğitim programından tam olarak memnun olmadıklarını ve tamamladıkları öğretmen eğitim programının aday öğretmenlerin ihtiyaçlarını karşılayamadığını göstermektedir. Çalışmanın sonuçlara dayanarak, Irak Kürdistan Bölgesel Yönetimi„nin öğretmen eğitimini iyileştirmek için bazı çıkarımlar ve ileriki çalışmalar için önerilerde bulunulmuştur.
Master of Arts in English Language Teaching (ELT). Thesis (M.A.)--Eastern Mediterranean University, Faculty of Education, Dept. of English Language Teaching, 2019. Supervisor: Assist. Prof. Dr. Fatoş Erozan.
Keywords: English Language Teaching (ELT); English Language--Study and Teaching--English Learning; Novice teachers; teachers’ perceptions; teacher education program; challenges; needs